2011
DOI: 10.1073/pnas.1012720108
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the cellular origin of squamous skin tumors

Abstract: Squamous cell carcinoma (SCC) is the second most frequent skin cancer. The cellular origin of SCC remains controversial. Here, we used mouse genetics to determine the epidermal cell lineages at the origin of SCC. Using mice conditionally expressing a constitutively active KRas mutant (G12D) and an inducible CRE recombinase in different epidermal lineages, we activated Ras signaling in different cellular compartments of the skin epidermis and determined from which epidermal compartments Ras activation induces s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
285
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(304 citation statements)
references
References 44 publications
17
285
0
2
Order By: Relevance
“…Mosaic activation of a constitutively active mutant of KRas (KRas LSL-G12D ) mimicking the natural occurrence of sporadic tumors in different compartments of the skin epidermis revealed the SCC-initiating cells (Fig. 5) (Lapouge et al 2011;White et al 2011). Papilloma formation was observed upon KRas G12D expression in bulge SCs and their progeny, but not in HF transit-amplifying cells.…”
Section: Squamous Cell Carcinomamentioning
confidence: 98%
See 3 more Smart Citations
“…Mosaic activation of a constitutively active mutant of KRas (KRas LSL-G12D ) mimicking the natural occurrence of sporadic tumors in different compartments of the skin epidermis revealed the SCC-initiating cells (Fig. 5) (Lapouge et al 2011;White et al 2011). Papilloma formation was observed upon KRas G12D expression in bulge SCs and their progeny, but not in HF transit-amplifying cells.…”
Section: Squamous Cell Carcinomamentioning
confidence: 98%
“…Although SG arises during morphogenesis from HF progenitors that may be common to bulge SCs, it is unclear whether bulge SCs participate in the normal renewal of the gland in the absence of pathological conditions. Lineage tracing using K15CREPR mice showed labeling of rare SG cells (Morris et al 2004), whereas Lgr5 (Jaks et al 2008) and K19CREER failed to label the SG during homeostasis Lapouge et al 2011). In contrast, during pathological conditions that stimulate SG proliferation such as oncogenic Ras expression (Lapouge et al 2011) or Blimp1 deletion (Horsley et al 2006), bulge SCs can contribute to the expansion of SG.…”
Section: Multipotency and Plasticity Of Epidermal Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that the expression of oncogenic KRas G12D coupled with genetic deletion of p53 deletion in interfollicular epidermal (IEF) cells was sufficient to elicit SCC with well-differentiated morphology; however, recapitulating these same genetic events in hair follicle (HF) cells resulted in SCC bearing multiple morphologies, including well-differentiated SCC, spindle cell SCC, and mixed morphology SCC (18,19). Such findings suggest that cell of origin and its unique genetic makeup ultimately determines the tumorigenic fate of distinct cell types to identical genetic events.…”
Section: Epigenetic Modulation Of Emt: Chromatin States Prime Cscs Fomentioning
confidence: 99%